THE EFFECT OF CLUSTERING TECHNIQUE ON STUDENTS’ WRITING ABILITY - Sumartini .; Hilda Puspita; Zahrida . (Universitas Bengkulu, 2018)
The research was aimed to investigate whether clustering technique can affect students’ writing ability. The research was conducted at the first year students of Senior High School number 8 Bengkulu. In conducting the research, the researcher applied a quasi experiment method with MIA 2 and MIA 1 as the sample. MIA 2 as an experimental group that consist of 24 students was taught by using clustering technique and MIA 1 as a control group that consist of 26. They were taught by conventional technique. Both of the groups were given pre-test at the beginning, the post test at the end of the treatment. The data were analyzed by using t-test formula. From the culculation, the reseacher found that t-count was 2.07 and t-table was 2.01. For T-count of organization was 2.56, t-count of content was 3.62 and t-count of coherent was 3.47. Since t-count was higher that t-table, it means H1 was accepted. So, it can be concluded that clustering technique affects students’ writing ability. In spesific, clustering technique improved students’ content, organization, and coherent text.